Analysis of Employee Work Productivity at PT Kinarya Mitra Sejahtera Sumedang - Gumilang, Risa Ratna; Gustiawati, Rani; Damayanti, Wulan Ariani; Nurjanah, Annisa Siti; Nurjanah, Mualif Fadilah (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2025)
Drug distribution is an important aspect in the health industry, because it plays a role in ensuring the availability of safe, quality, and timely drugs to the public. This study aims to evaluate the drug distribution system at PT Kinarya Mitra Sejahtera Sumedang, and to analyze the effectiveness and efficiency of distribution operations carried out. The research method used is a qualitative descriptive approach with observation and documentation study techniques. The results of the study indicate that the company has implemented the principles of Good Drug Distribution Practices (CDOB) and Standard Operating Procedures (SOP), but there are obstacles in recording drug inventory due to the unavailability of a batch code system. This has an impact on delays in the recording process and potential delays in delivery. The effectiveness and efficiency of distribution are greatly influenced by human resource (HR) management, where skilled and trained workers are able to improve performance and compliance with regulations. Therefore, the implementation of a batch code system is an important priority in order to increase work productivity and optimize distribution services. This study recommends the development of an integrated information system and HR training to support the success of drug distribution as a whole